(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This paper presents optimum path planning for multi mobile robots that move between an initial point toward a target point then back to the initial point in a way that avoid collision without heavily slow down robots speed. The work system designs for taking into consideration robots velocities as well as time that robots will spend it in their target points, since both could be variant for all robots. In order to achieve the work objectives, time and space method combined with sequential entry method are used to design robots motion. In addition, two priority levels are used of carefully selected priorities to avoid collision between robots; node level priority and robot level priority. In node level priority, the priority gives to robots in a manner that minimize the number of over all system collisions. While in robot level priority the priority gives to robots that cause faster speed for work achievement. The work is tested with different number of robots and different types of maps, and the algorithm proved its efficiency in finding the optimum solution regarding system performance for each robot in the collision points. The proposed algorithm is implemented using VBA programming language.